Effectiveness of Celebrity Endorsement Advertising in Chinese Marketplace - Gan, Wenqian (2006)
Celebrity endorsement is as the most prevalent advertising technique and strategy nowadays used in Chinese marketing communication to create positive effects in the minds of Chinese consumers, since competition of Chinese market has rapidly and increasingly intensified. In the meantime, celebrity endorsement in advertising has managerial significance, as it can be an effective competitive weapon in mature and saturated markets in order to support brand image and differentiate products form competitors. As little academic literatures have written in terms of effectiveness of celebrity endorsement in advertising within Chinese context, the main aim of my dissertation is to study the effectiveness of celebrity endorsement as a promotional technique within the Chinese marketplace through exploring the extent to which the celebrity endorsement influences Chinese consumer behaviours, identifying what factors that young Chinese consumers think of significantly influence effectiveness of celebrity endorsement, evaluating cultural influences to both Chinese consumers and selected celebrities as endorsers for marketers, and clarifying different attitude and perception to both Western and domestic celebrities endorsers existed among different young consumers groups due to such as differences of age and gender. This dissertation conducts a primary qualitative research method among Chinese young consumers to critically evaluate and provide insights with respect to effectiveness of celebrity endorsement in Chinese commercials based on previous academic literatures.